2010
DOI: 10.1016/j.marpolbul.2010.09.023
|View full text |Cite
|
Sign up to set email alerts
|

PCDD/Fs in sediments of Central Vietnam coastal lagoons: In search of TCDD

Abstract: Samples from nine Central Vietnam coastal lagoons, together with three soils and sediments collected in 24 two freshwater reservoirs of the Thua Thien-Hué province, were analysed for polychlorinated dibenzo-p- 25 dioxins and dibenzofurans (PCDD/Fs). Total concentrations are low, from 192 to 2912 pg g1 and depth 26 profiles in Tam Giang-Cau Hai (TG-CH) sediment cores show only minor changes over time in PCDD/F 27 input and composition. Octachloro dibenzo-p-dioxin (OCDD) is the prevailing congener (approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 49 publications
(75 reference statements)
3
9
1
Order By: Relevance
“…The total concentration of PCDDs (including: 1,3,6,1,3,7,2,3,7,1,2,3,7,1,2,3,4,7,1,2,3,6,7,1,2,3,7,8,1,2,3,4,6,7,HpCDD; and OCDD) ranged from 200 to 460 pg g -1 in 19 sediment core samples (Table 2, Figure 2). Comparison with an earlier study, the total concentration of PCDD/Fs in sediment cores collected from Thua Thien -Hue (Central Vietnam coastal lagoons) ranged 192 to 2910 pg g -1 (Piazza et al, 2010) which were 2 to 5 times higher than the results reported here. Kishida et al (2010) reported the total PCDDs in sediment collected from Can Gio, Thua Thien -Hue, and Hanoi ranging from 350 to 980 pg g -1 , and there was also higher concentration in sediments than reported here.…”
contrasting
confidence: 76%
See 2 more Smart Citations
“…The total concentration of PCDDs (including: 1,3,6,1,3,7,2,3,7,1,2,3,7,1,2,3,4,7,1,2,3,6,7,1,2,3,7,8,1,2,3,4,6,7,HpCDD; and OCDD) ranged from 200 to 460 pg g -1 in 19 sediment core samples (Table 2, Figure 2). Comparison with an earlier study, the total concentration of PCDD/Fs in sediment cores collected from Thua Thien -Hue (Central Vietnam coastal lagoons) ranged 192 to 2910 pg g -1 (Piazza et al, 2010) which were 2 to 5 times higher than the results reported here. Kishida et al (2010) reported the total PCDDs in sediment collected from Can Gio, Thua Thien -Hue, and Hanoi ranging from 350 to 980 pg g -1 , and there was also higher concentration in sediments than reported here.…”
contrasting
confidence: 76%
“…These results are 1000 times lower than another earlier study, the measured dl-PCBs concentrations in sediment from Saigon River Estuary, Vietnam ranged from 18 to 8400 pg g -1 (Shiozaki et al, 2009). However, the dl-PCBs were found in offshore sediment at the lower levels what compared with in sediments from the inlands and the coast from Vietnam in several previous reports (Minh et al, 2003;Kishida et al, 2010;Piazza et al, 2010).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…The results of a 2007 study of soil and water samples in the Ma Da area of III Corps, an area repeatedly sprayed with Agent Orange, did not provide evidence that the detected dioxins (mostly Octachlorodibenzo-p-dioxin, OCDD) that were bound to groundwater colloids were residues from the Vietnam War [24]. A very sophisticated study was reported by Piazza et al in 2010 of the analyses of sediments collected from nine Central Vietnam coastal lagoons [25]. Their conclusions: "Samples from nine Central Vietnam coastal lagoons, together with three soils and sediments collected in two freshwater reservoirs of the Thua Thien-Hue Province, were analyzed for polychlorinated dibenzo-pdioxins and dibenzofurans (PCDD/Fs).…”
Section: Assessment Of Potential Exposurementioning
confidence: 97%
“…However, recent sedimentary records in highly dynamic environments can be ineffective in providing continuous temporal patterns (Frignani et al 2007;Giuliani et al 2008Giuliani et al , 2011Piazza et al 2010). This is mainly due to the specific environment conditions that, for example in Central Vietnam coastal lagoons, alternate episodes of intense sediment removal (e.g., during typhoons) to others where huge amounts of detrital materials are transported to the lagoons by rivers (e.g., during floods).…”
Section: Introductionmentioning
confidence: 99%